Harnessing Students’ Creativity and Participatory Learning: A Step-by-Step Guide to Conducting Project-Based Digital Photovoice in ELT - AMANSYAH, Farida; NURHAYATI, Nurhayati (Research and Innovation in Applied Linguistics, 2025)
This "how-to" article presents a step-by-step guide to implementing a project-based digital photovoice in the context of English Language Teaching (ELT). While photovoice has been widely used as a pedagogical strategy in ELT, there is limited research on digital photovoice (DP) that integrates documentary photography, interviews, and web-based graphic design tools. Building on a series of DP initiatives, this article explores how DP-based instructions facilitate students' autonomous, authentic, flexible, collaborative, and participatory learning activities beyond the classroom. The process begins with engaging students in photo-taking activities, where they capture objects in their surroundings based on the project's theme. Subsequently, they conduct interviews with relevant informants to gather information about the objects. The students then analyze the images and interview data as primary sources to create the DP. Finally, they utilize Canva, a web-based graphic design tool, to produce the DP and share it digitally through social media applications. This approach has implications for integrating the DP project into Computer-Assisted Language Learning (CALL) innovation and pedagogy.